Spatial and temporal analysis of the collapse of the tailings dam in Brumadinho, Brazil - Leopoldino, Jéssica de Cássia; dos Anjos, Camila Souza; Simões, Débora Paula; Fernandes, Luiz Flávio Reis (Revista Agrogeoambiental, 2020)
Mining is an important economic activity in the world. Mining activities are known for their high environmental impacts. Considering the high magnitude of some operations and amounts of tailings produced, the mining activity has represented a risk for several regions and populations, which can be affected by accidents and inefficient disposal and monitoring systems. Remote sensing has been frequently used to map areas that are large or difficult to access; it enables the obtaining of information on objects or phenomena on the Earth’s surface without requiring physical contact, making it an important source of data collection that can be used for several purposes. Images used in remote sensing provide a synoptic and multitemporal view of large areas and are an alternative for environmental studies. The objective of this work was to evaluate the extension of the area affected by the collapse of the tailings dam of the Vale S.A. company in the Córrego do Feijão stream mine, in the municipality of Brumadinho, state of Minas Gerais, Brazil, which occurred on January 25, 2019, causing an environmental impact that will last for many years. The dimension of this environmental impact was analyzed using imagery of the Planet’s satellite constellation with spatial resolution of 3.0 meters. The methodology used was based on digital image processing, using the PCI Geomatics and ENVI 5.3 software, which made possible the quantification of the affected area. Two different methods were used and the results were compared to those provided by the State Secretariat for Environment and Sustainable Development of Minas Gerais, Brazil. The results showed an affected area of 2.964096 km², from the Brumadinho dam to the Paraopeba River.